Monitoring the AML1/ETO fusion transcript to predict outcome in childhood acute myeloid leukemia. Issue 10 (11th June 2014) - Zhang, Li; Cao, Zeng; Ruan, Min; Zeng, Qiang; Zhao, Liang; Li, Qinghua; Zou, Yao; Wang, Jianxiang; Zhu, Xiaofan
Abstract Background To determine the prognostic significance of the detection of the minimal residual disease (MRD) in children with AML1/ETO AML, we compared the results of reverse‐transcription polymerase chain reaction (RT‐PCR) and quantitative reverse‐transcription polymerase chain reaction (RQ‐PCR). Procedure Between January 2006 and February 2013, 70 patients (≤16 years of age) with AML1/ETO AML were included in our study. Bone marrow samples were evaluated using by both RT‐PCR and RQ‐PCR assays. AML1/ETO transcripts were normalized to 105 ABL copies. Results When treated with fewer than four courses of therapy, no association was found between positive RT‐PCR results and relapse. After four courses of therapy, a positive RT‐PCR result was correlated with a probability of relapse. After induction chemotherapy, a >1.8 log reduction in AML1/ETO transcripts in BM determined by RQ‐PCR may represent a subgroup of patients at low risk for relapse. MRD levels after consolidation (Courses 2 and 3) were also informative. Conclusion Both RT‐PCR and RQ‐PCR can be used to detect MRD in childhood AML1/ETO AML. RQ‐PCR can identify patients who are at high risk of relapse earlier than can RT‐PCR. Pediatr Blood Cancer 2014; 61:1761–1766. © 2014 Wiley Periodicals, Inc.